1985
DOI: 10.1002/j.1939-4640.1985.tb00827.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of White Blood Cells on the In Vitro Penetration of Zona‐free Hamster Eggs by Human Spermatozoa

Abstract: The presence of white blood cells in semen has been associated with male infertility. Previous studies indicate that pyospermia occurs in conjunction with decreases in sperm motility, number of normal sperm forms, and penetration rates in the zona-free hamster egg sperm penetration assay. We have evaluated the relationship of seminal white blood cells and sperm function, as reflected in the zona-free hamster egg penetration assay, and have investigated the possible mode of action of the white cells. Egg penetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
3

Year Published

1987
1987
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(39 citation statements)
references
References 15 publications
0
36
0
3
Order By: Relevance
“…In unstained wet preparations it is difficult to distinguish immature germ cells from WBC: Immature germ cells may be recorded as WBC. This might explain why Maruyama et al [58] found that among 243 ejaculates from infertile couples 134 contained high concentrations of WBC, i.e., >3 x 106/mL, and 42 ejaculates contained >I0 x 106/mL. Using cytological staining procedures the different kinds of NSC are distinguishable by morphological criteria.…”
Section: Cytological Staining Methodsmentioning
confidence: 99%
“…In unstained wet preparations it is difficult to distinguish immature germ cells from WBC: Immature germ cells may be recorded as WBC. This might explain why Maruyama et al [58] found that among 243 ejaculates from infertile couples 134 contained high concentrations of WBC, i.e., >3 x 106/mL, and 42 ejaculates contained >I0 x 106/mL. Using cytological staining procedures the different kinds of NSC are distinguishable by morphological criteria.…”
Section: Cytological Staining Methodsmentioning
confidence: 99%
“…The prevalence of LCS in male infertility patients varies from 2% to 40% in published reports (9,(11)(12)(13), and elevated concentrations of WBC in semen have been associated with reduced sperm function and quality (9,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of leukocytospermia to impairming the fertilizing ability of sperm was first studied in the mid-nineteen eighties 12 , but since then conflicting opinions have been expressed. For instance, Ochsendorf 8 stated that only very high numbers of leukocytes, at least >2.0x10 6 PMN per ml, generate excessive ROS which can not be counteracted by the antioxidant capacity of seminal plasma.…”
Section: Introductionmentioning
confidence: 99%